Digital Satellite Communications - Corazza, Giovanni E. (Information Technology: Transmission, Processing and Storage, 2007)
Digital Satellite Communications focuses on the study and design of efficient and flexible physical layers for broadband mobile and fixed satellite links. The chapters address long-term developments for advanced physical layer techniques in broadband communications, fixed and mobile terminals, and 4G evolutions with a potential convergence between different technologies. A general description of satellite systems and services is provided which organizes the material into a generalized and readable framework. The approach is both analytical and descriptive. The book provides a unified view of essential topics, including: · fundamental theories · channel coding and modulation · synchronization and parameter estimation · distortions and countermeasures · diversity techniques · multiplexing and multiple access schemes · software radio Digital Satellite Communications is ideal for researchers and students in the fields of communication and signal processing.